ANALISIS PERBEDAAN ABNORMAL RETURN DAN VOLUME PERDAGANGAN SAHAM SEBELUM DAN SETELAH PENGUMUMAN INDONESIA SUSTAINABILITY REPORTING AWARD (ISRA) (StudyEmpirisPada Perusahaan Go Publik Yang Listing di BEI PeraihPenghargaan ISRA Periode2009-2012) - Ranny Oktaviani, 10.05.52.0108; Wahyu Widati, Listyorini (Students Journal of Accounting and Banking, 2014)
This study was conducted to determine differences in abnormal returns and trading volume of the Indonesia Sustainability Reporting Award(ISRA) 2009-2012. This difference is seen from abnormal stock returns and trading volume before and after the announcement of Indonesia Sustainability Reporting Award(ISRA).In this study, the sample used is publicly traded company awarded Indonesia Sustainability Reporting Award ( ISRA ) 2009-2012 . The data used are secondary data consists of daily data abnormal stock returns and trading volume. Testing method is a paired t test ( paired t test ).The results of the study proved that there is no difference in abnormal returns before and after the announcement of ISRA 2009-2010. Stock trading volume has no difference before and after the announcement of ISRA 2009-2010.Keywords: sustainability report , sustainability reporting award Indonesia ,abnormal return , stock trading volume